The quinquennial review of the Switched Fixed Telephone Service’s (STFC) public regime agreements for the period 2011-2015 - Villela, Marina Cruz Vieira (Law, State and Telecommunications Review, 2009)
Telecommunication Sector Update on the quinquennial review of the Switched Fixed Telephone Service’s (STFC) public regime agreements.